Penerapan Model Probing Prompting Dengan Flash Card Untuk Meningkatkan Kemampuan Membaca Siswa Kelas III Sekolah Dasar - Huda, Asmaul; Prasasti, Pinkan Amita Tri (Universitas Muhammadiyah Magelang, 2023)
This research was carried out with the aim of helping third grade students at Jatisari 01 Public Elementary School in improving their reading skills using the application of the probing prompting model with flash cards. This research was compiled using Classroom Action Research (CAR) or Classroom Action Research (CAR). As many as 11 grade III students at SD Negeri Jatisari 01 were the subjects of this study. The results of students' reading ability are measured using predetermined criteria and indicators. The results showed that: in the first cycle students had an average reading ability of 17.8%, and the percentage level of mastery reached a moderate level. With a completeness level of 67.67% which fulfilled the researcher's target of 84%, in cycle II there was an increase in the average student's reading ability to 84.5% which was considered high. Based on the results of examining the data, it was concluded that the use of the probing prompting model with flash cards could improve the reading ability of class III students at SD Negeri Jatisari 01.